2 - La réforme LMD au Sénégal : le point de vue des étudiants - Diop, Babacar (Journal of Higher Education in Africa, 2022)
This article consists of a longitudinal survey carried in three of the six public universities in Senegal. It analyzes students’ point of view on the BMD/ Bachelor-Master-Doctor at reform initiated since 2003-2004 academic year. It highlights the key factors influencing the students’ perception of the implementation Bachelor-Master-Doctorate. In fact, their perception of the reform depends mainly on their programs or faculties as well as their level of studies and the university they attend. As a result, it can said that studies’ experiences are contextualized with the implementation of the reform in Senegal public universities.